The Nesbit tablets - Owen, David I. (Nisaba ;, 2016)
In 1914, William M. Nesbit published his dissertation at Columbia University on 30 archival texts from the Third Dynasty of Ur. Now, more than a century later, the remaining tablets in his collection have been recovered and, thanks to the generosity of the Nesbit family, were made available for publication by David I. Owen. The majority of texts published here is from Puzriš-Dagan (Drehem) with some from Nippur and Umma. They originate from the earliest clandestine finds at those sites. The 98 texts, including a re-edition of the previously published tablets, are provided with a catalogue, h.